P040 FIBROBLAST GROWTH FACTOR-INDUCIBLE 14 (FN14) SIGNALING MEDIATES CROHN'S DISEASE (CD)-LIKE ILEITIS IN SAMP MICE. (18th January 2018) - Martino, Luca Di; Pizarro, Theresa; Cominelli, Fabio
Abstract: Background: TNF-like Weak Inducer of Apoptosis (TWEAK) and Fn14 are TNF superfamily members that were reported to be elevated in colonic samples of UC patients. However, the precise role of TWEAK/Fn14 in intestinal inflammation is still not fully elucidated. The aim of this study was to determine the effects of genetic deletion of TWEAK/Fn14 in a model of CD-like ileitis (SAMP mice) as well as to analyze their levels in IBD patients compared to healthy controls (HC). Methods: Ileal biopsies were collected from IBD and HC patients and analyzed for TWEAK/Fn14 expression by qPCR and immunohistochemistry (IHC). Severity of ileitis was evaluated at 10, 20 and 30 weeks of age in SAMPxFn14-/- mice and WT littermates by a histological scoring system. Stereomicroscopy was used to assess the percentage of injured ileal mucosa. Results: Intestinal mRNA expression of Fn14 and TWEAK was significantly upregulated in CD patients with active inflammation by 5.1-fold and 5.9-fold, respectively, (p<0.05, n=15/group) compared to UC and HC. These results were confirmed by Western blot analysis, showing increased protein levels of TWEAK/Fn14 in CD samples compared to UC and HC. IHC showed increased staining of TWEAK in CD biopsies compared to UC and HC. Histological scoring showed that SAMPxFn14-/- mice had decreased disease severity compared to WT littermates (4.18 ± 1.55vs.10.40 ± 1.01; p<0.02, n≥10/group) at 20 weeks, (11.23 ± 4.27vs.16.30 ± 2.16; p<0.02, n≥10/group) at 30 weeks, but not at 10 weeks of age (5.78 ± 0.59 vs. 6.43 ± 0.33; p=ns, n≥18/group). Stereomicroscopic analysis of ilea confirmed the histological results. The weight percentage of mesenteric lymph nodes was diminished in SAMPxFn14-/- mice (0.140 ± 0.0844 vs. 0.282 ± 0.0835; p<0.05, n≥6/group). Conclusion: Our data indicate that Fn14 expression is increased in human CD and that Fn14 activation mediates intestinal inflammation in experimental ileitis; hence, blockade of Fn14 may serve as an innovative treatment for patients with IBD.